2008
DOI: 10.1017/s1047951108003399
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of 24 autopsied cases with supramitral rings

Abstract: The supramitral ring is a rare congenital malformation formed by presence of a ridge of connective tissue, usually attached at or above the mitral annulus. The incidence and clinical presentation is highly variable due to difficulty in diagnosis. A review of autopsied congenital heart diseases at our institute over a 17-year-period revealed 24 cases of supramitral ring. These were classified with respect to the morphology of the ridge and the presence of associated cardiac lesions. The ring was found in 1.5% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In our series, only two patients had isolated SMR (8%). Yaideeswar and colleagues [15] identified associated rheumatic MV abnormalities in three cases and there exists a possibility for the ridge to develop as a postinflammatory phenomenon.…”
Section: Discussionmentioning
confidence: 95%
“…In our series, only two patients had isolated SMR (8%). Yaideeswar and colleagues [15] identified associated rheumatic MV abnormalities in three cases and there exists a possibility for the ridge to develop as a postinflammatory phenomenon.…”
Section: Discussionmentioning
confidence: 95%
“…Supravalvar mitral ring . In their analysis of 1633 cases, Vaideeswar and colleagues reported that SMR had an incidence of 1.5% among all CHDs, which also accounted for 37.5% of those with an obstruction in the left‐side inflow tract …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, adhesion of the membrane to the valvar tissue may impair the opening of the leaflets; the ring may protrude into the mitral valve and cause obstruction . This congenital cardiac pathology is usually associated with other cardiac abnormalities and is described as one of the four components of the Shone's complex …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of cases are atypical with not all the components of the complex, and in those cases, the prognosis is better. Some cases are even diagnosed in adulthood [3][4][5]. For the most severe cases, the prognosis continues to be poor [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%